The Commons in an Age of Uncertainty : Decolonizing Nature, Economy, and Society - Obeng-Odoom, Franklin (Book collections on Project MUSE., 2021)
"In the last 200 years, the earth has increasingly become the private property of a few classes, races, transnational corporations, and nations. Repeated claims about the "tragedy of the commons" and the "crisis of capitalism" have done little to explain this concentration of land, encourage solution-building to solve resource depletion and, and address our current socio-ecological crisis. Presenting a new explanation, vision and action plan, The Commons in an Age of Uncertainty develops a new and hopeful theory centred on commoning the land. By commoning the land, rather than privatising it, the book develops the foundations for prosperity without destructive growth, and addresses both local and global challenges. A theory and vision of making the land the most fundamental priority of all commons does not only give hope, it also opens the doors to a new world in which economy, environment, and society are decolonised and liberated."--